2022
DOI: 10.1111/iej.13720
|View full text |Cite
|
Sign up to set email alerts
|

Effects of BMAL1 on dentinogenic differentiation of dental pulp stem cells via PI3K/Akt/mTOR pathway

Abstract: Aim: This study aimed to investigate the effect of the circadian clock gene Bmal1 on dentinogenic differentiation of dental pulp stem cells (DPSCs) under inflammatory conditions.Methodology: Dental pulp stem cells were isolated from the pulp tissue of the healthy donor and were then stimulated with different concentrations of lipopolysaccharide (LPS) to mimic inflammatory conditions. Real-time polymerase chain reaction was used to detect the gene expression of circadian clock genes Bmal1, Clock, Per1, Per2, Cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Odontoblasts are the target cells of various hormones, and these hormones are regulated by clock genes, indicating that odontogenesis is regulated by the circadian clock from the perspective of hormone levels ( Zheng et al, 2014 ). In the three different embryonic phases of murine dental pulp cells, only Clock, Pers, and Bmal1 at low but variable levels were detected ( Xu et al, 2022 ). Rev-erbαshowed oscillated expression in a 24 h cycle in cementoblast cell line OCCM-30, which suggested the circadian rhythms exist in cementoblasts.…”
Section: Circadian Rhythm/clock Genes Regulate Maxillofacial Embryoni...mentioning
confidence: 99%
See 1 more Smart Citation
“…Odontoblasts are the target cells of various hormones, and these hormones are regulated by clock genes, indicating that odontogenesis is regulated by the circadian clock from the perspective of hormone levels ( Zheng et al, 2014 ). In the three different embryonic phases of murine dental pulp cells, only Clock, Pers, and Bmal1 at low but variable levels were detected ( Xu et al, 2022 ). Rev-erbαshowed oscillated expression in a 24 h cycle in cementoblast cell line OCCM-30, which suggested the circadian rhythms exist in cementoblasts.…”
Section: Circadian Rhythm/clock Genes Regulate Maxillofacial Embryoni...mentioning
confidence: 99%
“…Dental pulp-derived stem cells show rhythmic oscillations of Bmal1, Rer-erbα, and Per2 under mechanical stretching ( Tao et al, 2016 ). Dysfunction of the circadian clock affects dentin apposition and mineralization, the effects of BMAL1 on dentinogenic differentiation of DPSCs via PI3K/Akt/mTOR pathway ( Xu et al, 2022 ), but the additional specific mechanisms underlying differential expression of circadian clock genes on tooth development needs to be further studied ( Figure 2 ).…”
Section: Circadian Rhythm/clock Genes Regulate Maxillofacial Embryoni...mentioning
confidence: 99%
“…PI3K/AKT pathway has been demonstrated to play a positive role in migration and proliferation of stem cells by mediating actin cytoskeleton reorganization [33] and upregulating the expression of proteins that regulate cellular processes like cyclin D1 [34]. Additionally, PI3K/AKT pathway is involved in the differentiation of stem cells by regulating downstream signals including SOX2 [35], mTOR [36] and GSK3β [37]. Accumulating evidence suggests that activating the PI3K/AKT pathway can contribute to osteogenesis [38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al. reported that the PI3K/Akt/mTOR pathway regulates odontogenic differentiation of DPSCs via the effect of Bmal [47]. Al‐Habib et al.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the mTOR signaling pathway modulates the lineage differentiation of mesenchymal stem cells, including osteogenesis, adipogenesis, and myogenesis [46]. Xu et al reported that the PI3K/Akt/mTOR pathway regulates odontogenic differentiation of DPSCs via the effect of Bmal [47]. Al-Habib et al reported that inhibition of the mTOR pathway diminishes odontogenic/osteogenic, adipogenic, and neurogenic differentiation of DPSCs [48].…”
Section: Discussionmentioning
confidence: 99%